Modes of Operation, Design, and Experiments in a Laboratory Solar Convective Furnace System - Kumar V.D.; Chandra L.; Sharma P.; Shekhar R. (My University, 2025)
The concept of a laboratory-scale solar convective furnace system (SCFS) has been proposed in a previous publication (Patidar et al. in JOM 67:2696–2704, 2015). In the present work, hot air generated from concentrated solar radiation heats ingots in an aluminium soaking furnace. The SCFS consists of the following components: an open volumetric air receiver (OVAR) to heat ambient air, thermal energy storage to address the intermittency of solar radiation, and a retrofitted soaking furnace. The TES is charged by hot air from the OVAR. Hot air recovered from the TES heats ingots in the retrofitted furnace. The present paper has three objectives. First, the modes of operation of a SCFS will be explored. Herein, the possible circuits which depict the interconnection between the components of a SCFS for day and night operations will be discussed. Second, the design basis and results of a laboratory-scale SCFS will be shown. Third, a preliminary mathematical model of a SCFS circuit will be presented. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.